The Limits to Equivalent Living Conditions: Regional Disparities in Premature Mortality in Germany - Laroze-Prehn, D (Springer Verlag, 2018)
Aim: Despite the country’s explicit political goal to establish equivalent living conditions across Germany, significant inequality continues to exist. We argue that premature mortality is an excellent proxy variable for testing the claim of equivalent living conditions since the root causes of premature death are socioeconomic. Subject and methods: We analyse variation in premature mortality across Germany’s 402 districts and cities in 2014. Results: Premature mortality spatially clusters among geographically contiguous and proximate districts/cities and is higher in more urban places as well as in districts/cities located further north and in former East Germany. We demonstrate that, first, socioeconomic factors account for 62% of the cross-sectional variation in years of potential life lost and 70% of the variation in the premature mortality rate. Second, we show that these socioeconomic factors either entirely or almost fully eliminate the systematic spatial patterns that exist in premature mortality. Conclusion: On its own, fiscal redistribution, the centrepiece of how Germany aspires to establish its political goal, cannot generate equivalent living conditions in the absence of a comprehensive set of economic and social policies at all levels of political administration, tackling the disparities in socioeconomic factors that collectively result in highly unequal living conditions. © 2017, The Author(s).